DIKSI DALAM PIDATO POLITIK: STUDI KASUS PEMILIHAN KATA PADA KAMPANYE PEMILU - Jimly Sahbana Harahap; Mega Dewi Ambarwati (JURNAL ILMIAH NUSANTARA, 2025)
This study aims to analyze the impact of climate change on agricultural productivity in tropical regions and identify effective adaptation strategies to enhance the resilience of the agricultural sector. The methodology employed includes both qualitative and quantitative approaches through surveys, in-depth interviews, and secondary data analysis from weather reports and agricultural statistics. The findings reveal that changes in rainfall patterns and rising temperatures have significantly affected crop yields, with an average decrease of 20%. Factors such as access to agricultural technology, water resources, and crop diversification play crucial roles in successful adaptation. Strategies such as the implementation of modern irrigation systems and climate-resistant crop breeding have proven effective in mitigating the negative impacts of climate change. The conclusion of this study recommends improvements in adaptation policies based on local food security conditions.